The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fspor.2022.809092
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of the Community-Based Sports Club Environment on the Support and Development of Volunteer Women Coaches in Ireland

Abstract: In Ireland, the majority of coaches at non-elite level are volunteers and within the female-only team sport of women's Gaelic football, most qualified coaches are women. Yet, little is known on the club specific experiences of volunteer women coaches in non-elite sport. To address this gap, 11 women coaches, from three Gaelic Football clubs, were interviewed to explore the influence of the community-based club environment on their support and development in the role. The participants were actively coaching and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Some examples of public health-related work on Gaelic games include an effective physical activity motivation programme for younger girls 3 ; and the effects of community support on women volunteer coaches. 4 There is one very large study of coaches, which found that coaches spent almost 10 h a week on club-related activity, a large majority had a coaching qualification, and that about one in five were women. 5 These are all clear benefits.…”
mentioning
confidence: 99%
“…Some examples of public health-related work on Gaelic games include an effective physical activity motivation programme for younger girls 3 ; and the effects of community support on women volunteer coaches. 4 There is one very large study of coaches, which found that coaches spent almost 10 h a week on club-related activity, a large majority had a coaching qualification, and that about one in five were women. 5 These are all clear benefits.…”
mentioning
confidence: 99%